Legal sustainability and biosecurity of fish farms in the municipality of Capitão Poço - PA (Research, Society and Development, 2022)
The regularization or legalization of fish farming ventures is an important tool for directing the activity, as it aims at economic viability with environmental sustainability. However, it is important to emphasize that in fish farming, as in other work activities, workers are exposed to environmental risks. The objective of this work was to characterize the fish farming developed in the Municipality of Capitão Poço - PA, analyzing the environmental aspects and the safety of the workers. Data collection was carried out through interviews with fish farmers, who are distributed both in the urban and rural areas of the municipality. Semi-structured questionnaires containing 66 open and closed questions were applied. After two days of field research carried out in 10 enterprises in the municipality, lasting an average of one to two hours per visit in order to obtain, through graphs, tables and figures, a statistical scenario that synthesizes the information obtained in the field. From the data collected, a socioeconomic profile of the producers can be traced, in addition, a brief analysis of these results allowed to identify some agents of health risks of the workers and also the main problems for the environmental regularization of the producers. It is possible to say that fish farmers are in an occupational group that is very exposed to accidents and diseases, therefore, it is essential to promote informative and educational campaigns to raise their awareness. In addition to technical assistance for the implementation of fish farming and clarification on licensing issues, size of the enterprise and effluent treatment, since most fish farms were classified as PM severity, they did not have decanting tanks and fish farmers said they were legalized. . However, the research showed that they did not have the license and confused being legalized with having the CAR, which according to the new Forest Code is not enough to be environmentally regularized.